Intratracheal Administration of Small Interfering RNA Targeting Fas Reduces Lung Ischemia-Reperfusion Injury*. Issue 8 (August 2016) - Del Sorbo, Lorenzo; Costamagna, Andrea; Muraca, Giuseppe; Rotondo, Giuseppe; Civiletti, Federica; Vizio, Barbara; Bosco, Ornella; Martin Conte, Erica L.; Frati, Giacomo; Delsedime, Luisa; Lupia, Enrico; Fanelli, Vito; et al.
Abstract : Objectives: Lung ischemia-reperfusion injury is the main cause of primary graft dysfunction after lung transplantation and results in increased morbidity and mortality. Fas-mediated apoptosis is one of the pathologic mechanisms involved in the development of ischemia-reperfusion injury. We hypothesized that the inhibition of Fas gene expression in lungs by intratracheal administration of small interfering RNA could reduce lung ischemia-reperfusion injury in an ex vivo model reproducing the procedural sequence of lung transplantation. Design: Prospective, randomized, controlled experimental study. Setting: University research laboratory. Subjects: C57/BL6 mice weighing 28–30 g. Interventions: Ischemia-reperfusion injury was induced in lungs isolated from mice, 48 hours after treatment with intratracheal small interfering RNA targeting Fas, control small interfering RNA, or vehicle. Isolated lungs were exposed to 6 hours of cold ischemia (4°C), followed by 2 hours of warm (37°C) reperfusion with a solution containing 10% of fresh whole blood and mechanical ventilation with constant low driving pressure. Measurements and Main Results: Fas gene expression was significantly silenced at the level of messenger RNA and protein after ischemia-reperfusion in lungs treated with small interfering RNA targeting Fas compared with lungs treated with control small interfering RNA or vehicle. Silencing of Fas gene expression resulted in reduced edema formation (bronchoalveolar lavage protein concentration and lung histology) and improvement in lung compliance. These effects were associated with a significant reduction of pulmonary cell apoptosis of lungs treated with small interfering RNA targeting Fas, which did not affect cytokine release and neutrophil infiltration. Conclusions: Fas expression silencing in the lung by small interfering RNA is effective against ischemia-reperfusion injury. This approach represents a potential innovative strategy of organ preservation before lung transplantation.